The Most Common Characteristics of Fragile Video Watermarking: A Review - Hassan, Yasmin A.; Rahma, Abdul Monem S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
The progress of network and multimedia technologies has been phenomenal during the previous two decades. Unauthorized users will be able to copy, retransmit, modify reproduction, and upload the contents more easily as a result of this innovation. Malicious attackers are quite concerned about the development and widespread use of digital video. Digital watermarking technology gives solutions to the aforementioned problems. Watermarking methods can alleviate these issues by embedding a secret watermark in the original host data, allowing the genuine user or file owner to identify any manipulation. In this study, lots of papers have been analyzed and studied carefully, in the period 2011–2022. The historical basis of the subject should not be forgotten so studying old research will give a clear idea of the topic. To aid future researchers in this subject, we give a review of fragile watermarking approaches and some related papers presented in recent years. This paper presents a comparison of many relevant works in this field based on some of the outcomes and improvements gained in these studies, which focuses on the common characteristics that increase the effect of watermarking techniques such as invisibility, tamper detection, recovery, and security